The Correlation Between ApoE Genetic Polymorphism and Serum Lipid Levels - Tang, Yishu; Yang, Yang (Cardiology and Cardiovascular Medicine, 2018)
Objective: To explore the correlation between apolipoprotein E genetic polymorphism and serum lipid levels. Methods: The genechips method was adopted to detect the ApoE genotype in people undergoing physical examination.The serum lipid levels were compared among the populations with different ApoE genotypes. Results: The ApoE gene showed the polymorphic distribution in populations,in which the distribution frequency of E3 allele was highest,the population containing E2 allele had higher triglyceride level in serum, the population containing E4 allele had higher total cholesterol level in serum. Conclusion: The ApoE gene presents the polymorphic distribution in populations. The E2 allele is correlated with serum high triglyceride level. The E4 allele correlated with serum high total cholesterol level.